In adenosine A2B knockouts acute treatment with inorganic nitrate improves glucose disposal, oxidative stress, and AMPK signaling in the liver - Peleli, Maria; Hezel, Michael; Zollbrecht, Christa; Persson, A. Erik G.; Lundberg, Jon O.; Weitzberg, Eddie; Fredholm, Bertil B.; Carlstrom, Mattias (Frontiers in Physiology, 2015)
Rationale: Accumulating studies suggest that nitric oxide (NO) deficiency and oxidative stress are central pathological mechanisms in type 2 diabetes (T2D). Recent findings demonstrate therapeutic effects by boosting the nitrate-nitrite-NO pathway, which is an alternative pathway for NO formation. This study aimed at investigating the acute effects of inorganic nitrate on glucose and insulin signaling in adenosine A2B receptor knockout mice (A−/−2B), a genetic mouse model of impaired metabolic regulation. Methods: Acute effects of nitrate treatment were investigated in aged wild-type (WT) and A−/−2B mice. One hour after injection with nitrate (0.1 mmol/kg, i.p.) or placebo, metabolic regulation was evaluated by intraperitoneal glucose and insulin tolerance tests. NADPH oxidase-mediated superoxide production and AMPK phosphorylation were measured in livers obtained from non-treated or glucose-treated mice, with or without prior nitrate injection. Plasma was used to determine insulin resistance (HOMA-IR) and NO signaling. Results: A−/−2B displayed increased body weight, reduced glucose clearance, and attenuated overall insulin responses compared with age-matched WT mice. Nitrate treatment increased circulating levels of nitrate, nitrite and cGMP in the A−/−2B, and improved glucose clearance. In WT mice, however, nitrate treatment did not influence glucose clearance. HOMA-IR increased following glucose injection in the A−/−2B, but remained at basal levels in mice pretreated with nitrate. NADPH oxidase activity in livers from A−/−2B, but not WT mice, was reduced by nitrate treatment. Livers from A−/−2B displayed reduced AMPK phosphorylation compared with WT mice, and this was increased by nitrate treatment. Finally, injection with the anti-diabetic agent metformin induced similar therapeutic effects in the A−/−2B as observed with nitrate. Conclusion: The A−/−2B mouse is a genetic mouse model of metabolic syndrome. Acute treatment with nitrate improved the metabolic profile in it, at least partly via reduction in oxidative stress and improved AMPK signaling in the liver.